Practice and Theory of Automated Timetabling VI
DOI: 10.1007/978-3-540-77345-0_13
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Solution of a Complex University Course Timetabling Problem

Abstract: The modeling and solution approaches being used to automate construction of course timetables at a large university are discussed. A course structure model is presented that allows this complex real-world problem to be described using a classical formulation. The problem is then tackled utilizing a course timetabling solver model that transforms it into a constraint satisfaction and optimization problem. The tiered structure of this approach provides flexibility that is helpful in solving the multiple subprobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 15 publications
0
34
0
Order By: Relevance
“…Specific to conference scheduling, Sampson et al [9] introduced formulations for maximizing the number of talks of interest attendees can attend. For the related problem of course scheduling, Murray et al [6] introduced formulations for minimizing student and instructor conflicts subject to scheduling constraints. While automated scheduling is appropriate when the parameters and constraints of the optimization problem are well-specified, our interviews with past CHI organizers suggest a need for mixed-initiative, interactive optimization [4,10] that engage organizers to tackle soft considerations and tacit constraints.…”
Section: Related Workmentioning
confidence: 99%
“…Specific to conference scheduling, Sampson et al [9] introduced formulations for maximizing the number of talks of interest attendees can attend. For the related problem of course scheduling, Murray et al [6] introduced formulations for minimizing student and instructor conflicts subject to scheduling constraints. While automated scheduling is appropriate when the parameters and constraints of the optimization problem are well-specified, our interviews with past CHI organizers suggest a need for mixed-initiative, interactive optimization [4,10] that engage organizers to tackle soft considerations and tacit constraints.…”
Section: Related Workmentioning
confidence: 99%
“…Obviously, if the conflict graph is |P |-colourable, a proper colouring is found. Such a model is employed, for instance, at Purdue University (Rudová & Murray, 2003;Murray, Müller, & Rudová, 2007).…”
Section: An Application In Course Timetablingmentioning
confidence: 99%
“…Nevertheless, some authors claim that few papers applying models and methods using instances of real-world data (Carter & Laporte, 1998;McCollum, 2007;Murray et al, 2007) can be found. These authors note that many articles concentrate on developing solutions to simplified problems, or that they use artificial data sets, and rarely extend their solutions to large scale formulations.…”
Section: Introductionmentioning
confidence: 99%